An Analysis of the Role of Intelligence Games in Policies Aimed at Fighting Gaming Addiction - Dağlı, Zülkif (Addicta: The Turkish Journal on Addictions, 2020)
The objective of this study is to analyze the relationship of gaming addiction tendencies for students studying in schools with intelligence games course compared to those without and to start a conceptual discussion. The study adopts the quantitative approach with data being collected using a questionnaire. The study has been conducted during the 2019 spring semester. The study sample includes students in equal numbers from the same socio-economic levels and from schools with and without intelligence games courses in Düzce’s city center. A total of 1,870 students have been analyzed within the scope of the study. The study’s results indicate that the students studying in schools with an intelligence games course are less likely to develop gaming addiction. Accordingly, intelligence games courses may be used successfully in the fight against gaming addiction. Those who prefer online games can further be argued to be more likely to develop gaming addiction, which leads us to the conclusion that online games are a critical element in the development of gaming addiction. Finally, the study has revealed male students to be more likely to develop gaming addictions than female students. Therefore, gender and online gaming should be considered as the risk factors for game addiction.
Keywords: Gaming addiction; intelligence games; intelligence games course; internet addiction